The supervision of the treatment of ICT in educational centers - Cornax Castillo, Juan Carlos; del Río Palomino, José Miguel; Sánchez Alcántara, José Daniel (Avances en Supervisión Educativa, 2013)
The development of competentes related to information and communication technologies (ICT) is found in all levels of our educational system. Therefore, within the supervision framework, this being one the competences of education inspectors, it becomes necessary to have a tool which guides the intervention in order to check the work being done in schools on ICT, focusing on teaching practice. This article offers a proposal of elements and processes to be supervised related to ICT in the educational sphere.